Pengaruh Usia dan Masa Kerja terhadap Produktivitas Kerja Karyawan di Rumah Sakit Islam Ibnu Sina Bukittinggi - Yulianti, Penny; Bila, Aziza; Putri Oktaviane, Diga (PUBLICNESS: Journal of Public Administration Studies, 2023)
Productivity is a comparison between the results of an employee's work with the sacrifices that have been spent. Increasing work productivity is possible only by humans. Therefore labor is an important factor in measuring productivity. Age and length of service are factors that are directly related to work productivity. Age and length of service felt by employees can reduce productivity or increase employee work productivity. This study was conducted at the Ibnu Sina Bukittinggi Islamic Hospital, aiming to determine the effect of age and working period on employee work productivity. The data collection used in this study was by using questionnaires. The population in the study was 212 employees of the Ibn Sina Bukittinggi Islamic Hospital. In this study using quantitative methods with a descriptive approach. As independent variables, namely age and length of work, while dependent variables are labor productivity. The results of the data analysis obtained that the variables of age and length of service have a positive effect on work productivity, this can be seen from the results of the analysis of the coefficient of determination R2 (R square) showing that the percentage of contribution of the influence of independent variables (Age and Working Period) is 33.1% on the work productivity of employees of Ibnu Sina Bukittinggi Islamic Hospital.